Frozen state conditions for exponential consensus of time-varying cooperative nonlinear networks - Manfredi,S; Angeli,D (Automatica, 2015)
In this paper we present new results on exponential consensus for continuous-time nonlinear time varying cooperative networks. We endow the well known assumption of integral connectivity proposed by Moreau with a remarkable additional feature of being frozen in state variables, making its direct verification more straightforward. Moreover, we give an estimate of the exponential rate of convergence towards the agreement space. Finally, the proposed results are validated for representative examples.